Characterization of Modification Patterns, Biological Function, Clinical Implication, and Immune Microenvironment Association of m6A Regulators in Pancreatic Cancer - Fang, Kun; Qu, Hairong; Wang, Jiapei; Tang, Desheng; Yan, Changsheng; Ma, Jiamin; Gao, Lei (Frontiers in Genetics, 2021)
Objective: N6-methyladenosine (m6A) modification may modulate various biological processes. Nonetheless, clinical implications of m6A modification in pancreatic cancer are undefined. Herein, this study comprehensively characterized the m6A modification patterns in pancreatic cancer based on m6A regulators. Methods: Genetic mutation and expression pattern of 21 m6A regulators and their correlations were assessed in pancreatic cancer from TCGA dataset. m6A modification patterns were clustered using unsupervised clustering analysis in TCGA and ICGC datasets. Differences in survival, biological functions and immune cell infiltrations were assessed between modification patterns. A m6A scoring system was developed by principal component analysis. Genetic mutations and TIDE scores were compared between high and low m6A score groups. Results: ZC3H13 (11%), RBM15B (9%), YTHDF1 (8%) and YTHDC1 (6%) frequently occurred mutations among m6A regulators. Also, most of regulators were distinctly dysregulated in pancreatic cancer. There were tight crosslinks between regulators. Two m6A modification patterns were constructed, with distinct prognoses, immune cell infiltration and biological functions. Furthermore, we quantified m6A score in each sample. High m6A scores indicated undesirable clinical outcomes. There were more frequent mutations in high m6A score samples. Lower TIDE score was found in high m6A score group, with AUC=0.61, indicating that m6A scores might be used for predicting the response to immunotherapy. Conclusion: Collectively, these data demonstrated that m6A modification participates pancreatic cancer progress and ornaments immune microenvironment, providing an insight into pancreatic cancer pathogenesis and facilitating precision medicine development.